2021
DOI: 10.3390/ijgi10020087
|View full text |Cite
|
Sign up to set email alerts
|

A Data Cube Metamodel for Geographic Analysis Involving Heterogeneous Dimensions

Abstract: Due to their multiple sources and structures, big spatial data require adapted tools to be efficiently collected, summarized and analyzed. For this purpose, data are archived in data warehouses and explored by spatial online analytical processing (SOLAP) through dynamic maps, charts and tables. Data are thus converted in data cubes characterized by a multidimensional structure on which exploration is based. However, multiple sources often lead to several data cubes defined by heterogeneous dimensions. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…Afin de permettre des interactions, notamment par comparaisons et recoupements, entre cubes de données raster et vectoriels, l'outil est conceptualisé sur base d'un métamodèle unique (Kasprzyk et Devillet, 2021) permettant la navigation dans une constellation de cubes aux dimensions hétérogènes. Dans notre cas d'étude, cette hétérogénéité concerne les dimensions spatiales du SOLAP pouvant être géographiques (vectorielles) ou géométriques (raster).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Afin de permettre des interactions, notamment par comparaisons et recoupements, entre cubes de données raster et vectoriels, l'outil est conceptualisé sur base d'un métamodèle unique (Kasprzyk et Devillet, 2021) permettant la navigation dans une constellation de cubes aux dimensions hétérogènes. Dans notre cas d'étude, cette hétérogénéité concerne les dimensions spatiales du SOLAP pouvant être géographiques (vectorielles) ou géométriques (raster).…”
Section: Discussionunclassified
“…Pour fonctionner avec plusieurs cubes de données, un outil SOLAP nécessite la définition des différents concepts manipulés au sein du système : cubes de données, dimensions, dimensions géographiques, hiérarchies, mesures, etc. Cette définition passe par un métamodèle (Boulil et al, 2011 ;Kasprzyk et Devillet, 2021 ;OMG, 2003) qui, une fois implémenté, permet le stockage de toutes les métadonnées des cubes afin de les explorer à travers les opérations SOLAP.…”
Section: Métamodèles Solapunclassified
“…It demonstrated that data cube descriptive models can be used for the easy integration of heterogeneous data and SOLAP navigation in complex towers of data cubes. In [42], the study proved that the combination of both OLAP and data mining provides excellent solutions. OLAP mining databases enhance data mining and analysis capabilities directly into the database server.…”
Section: Literature Reviewmentioning
confidence: 96%